Formal specification of ADACOR holonic control system : coordination models - Paulo Leitão (2005)
The formal specification of agent-based and holonic manufacturing control systems assumes a critical role in order to understand and synthesize those complex systems. This paper presents the formal specification of the coordination models for the ADACOR holonic control system. For this purpose, it is used High-Level Petri Nets to model the behaviour of individual ADACOR entities, AUML interaction diagrams to represent the interaction between those entities and mailboxes structures to synchronize the evolution of the Petri net models.